Studi Komparasi Capaian Keterampilan Komunikasi Siswa Antara Penerapan Model Kooperatif Tipe Jigsaw Disertai Praktikum dengan Model Guided Discovery pada Siswa Kelas XI IPA SMAN 3 Boyolali Tahun Ajaran 2016/2017 - Annisa Aul Aeni; Joko Ariyanto; Slamet Santoso (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The purpose of this research is to examine the comparation of student communication skills achivement between the implementation of cooperative jigsaw combined whit practicum and implementation of guided discovery learning in student grade XI IPA SMAN 3 Boyolali. This research is quantitatif research and tend quasy-experimental. Sampling technique using a cluster sampling and used normality and homogenity test as the prerequisites test. Selected samples were XI science 4, XI science 1 and XI science 2. Grade XI science 4 as control class with conventional model, XI science 1 as first experiment class that used jigsaw model with practicum, and XI science 2 as second experiment class with guided discovery learning. Data collection used documentation and observation method. Data was analyzed by One Way ANOVA test with level significance 5% (α = 0,05) and Tukey HSD test as advanced test. Prosedure of the research were preparation, implementation and analyzing. The result of the research there is difference between student communication skills between cooperative jigsaw with practicum and guided dicovery learning in student grade XI science SMAN 3 Boyolali academic year 2016/2017. Implementation of cooperative jigsaw with practicum sensitive to oral communication at the oral presentation stage so it can be used to train speaking skills, while the guided discovery learning sensitive with oral communication at the orientation and discuccion stage so it can be used to train listening and interpersonal communication skills.